2010
DOI: 10.1183/09031936.00114709
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of dietary patterns with adult lung function and COPD

Abstract: Previous studies of diet and lung function have focused on associations with individual nutrients and foods, and not dietary patterns.The relationships between dietary patterns and lung function and spirometrically defined chronic obstructive pulmonary disease (COPD) were investigated in 1,551 males and 1,391 females in Hertfordshire, UK. Dietary information was obtained by food frequency questionnaire and dietary patterns were identified using principal components analysis.Using regression analysis, after con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 57 publications
10
113
0
1
Order By: Relevance
“…Multicollinearity issues are so resolved and PCA has been used recently for this purpose [26,27]. The new variables, called ''components'' in PCA terminology, are linear combinations of the original ones.…”
Section: Discussionmentioning
confidence: 99%
“…Multicollinearity issues are so resolved and PCA has been used recently for this purpose [26,27]. The new variables, called ''components'' in PCA terminology, are linear combinations of the original ones.…”
Section: Discussionmentioning
confidence: 99%
“…9 Since 2007, a few reports have been published on the association between dietary patterns and asthma/COPD. [10][11][12][13][14][15][16] Among these studies,…”
Section: Introductionmentioning
confidence: 99%
“…Either way, recent studies of dietary patterns also have shown associations with lung health. Out of five studies looking at the association between dietary patterns with spirometry or COPD symptoms or incidence [5][6][7][8][9], three studies reported a ''protective'' association for a ''prudent'' dietary pattern characterised by a high intake of fruit, vegetables, fish and wholegrain cereals [5,8,9], consistent with the dietary antioxidant or antiinflammatory properties hypothesis. Moreover, four studies (out of the five) also reported a deleterious effect of a ''Western'' diet characterised by a high intake of chicken, pork, fish, rice and noodle dishes, and preserved foods among a population of Chinese Singaporeans [7], by a high intake of cured and red meat, potato, boiled vegetables, added fat, coffee and beer among Dutch adults [6], and by a high intake of cured and red meats, refined grains, desserts, sweets, French fries and high-fat dairy products among adults in the USA [8,9].…”
Section: @Erspublicationsmentioning
confidence: 75%